Bovine thrombin enhances the efficiency and specificity of polymerase chain reaction - Zhang, Ying (BioTechniques, 2014)
The polymerase chain reaction (PCR) has become one of the central techniques in molecular biology since its invention. However, PCR can be fraught with difficulties in various situations, and it is desirable to find novel PCR enhancers suitable for universal applications. Here we show that bovine thrombin (BT), a well-known coagulation protein, is exceptionally effective at preventing the formation of primer dimers and enhancing the formation of the desired PCR products. The PCR enhancement effects of BT were demonstrated by testing various types of samples, including low-copy synthetic single-stranded DNAs (ssDNAs), synthetic ssDNA pools, human genomic DNA, and hepatitis B virus genomic DNA. In addition, BT was also able to effectively relieve PCR inhibition by nanomaterial inhibitors such as gold nanoparticles (AuNPs) and graphene oxide (GO). Compared with BSA, one of the most popular PCR enhancers, BT was more effective and required concentrations 18-178 times less than that of BSA to achieve a similar level of PCR enhancement